Varied etiologies and management of recurrent hypoglycemia in children: a case series - Ranabijuli, Pradeep Kumar; L. A., Nazparveen; Rajesh, T.; Ganesh, Kawle (International Journal of Contemporary Pediatrics, 2025)
Recurrent hypoglycemia in childhood may be caused by various endocrine or metabolic disorders. We present a series of five cases with recurrent episodes of hypoglycemia. The critical blood samples of all the cases were sent for the diagnosis of recurrent episodes of hypoglycemia. Neuroimaging of the brain was done to determine the size and location of the pituitary gland. In our case series, three cases were diagnosed as panhypopituitarism, and the other two were diagnosed by exclusion as idiopathic hyperketotic hypoglycemia. In our case series, no child was detected to have a metabolic cause of hypoglycemia. This case series provides insight for the diagnosis and management of recurrent episodes of hypoglycemia in children beyond infancy.